Cinema Africa 24/25 - Interview with "Dilli Dark"' main actor Samuel Robinson (Cinema Africa 2024/25, 2024)
Samuel Abiola Robinson was our guest for the November edition of the Cinema Africa film festival 2024/25. The Nigerian actor stars in the movie "Dilli Dark" that was presented on 11.11.2024 in Cineplex Bayreuth. Before Robinson was present for the screening and subsequent discussion, he sat with the festival's organiser Prof. Dr. Ute Fendler for an interview talking about his career, life in New Delhi and forthcoming projects.